2020
DOI: 10.1055/a-1195-2737
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced Nitric Oxide Contributes to Spatial Memory and Hippocampal Capillaries in Rats

Abstract: AbstractExercise has been argued to improve cognitive function in both humans and rodents. Angiogenesis significantly contributes to brain health, including cognition. The hippocampus is a crucial brain region for cognitive function. However, studies quantifying the capillary changes in the hippocampus after running exercise are lacking. Moreover, the molecular details underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…They detected an increase in the eNOS activity and number of EPCs in these treated mice. However, eNOS-deficient mice treated with the same exercise regimen did not show these beneficial changes [ 106 , 181 , 182 ]. Moderate physical exercise has been shown to stimulate the expression of endogenous antioxidants such as SOD, GRx, and GR; reduce the activity of NADH oxidase; and reduce the production of inflammatory cytokines such as IL-6 and TNF-α, thereby limiting the spread of oxidative stress [ 183 , 184 ].…”
Section: Nos/no Pathway-involved Vad Therapiesmentioning
confidence: 99%
“…They detected an increase in the eNOS activity and number of EPCs in these treated mice. However, eNOS-deficient mice treated with the same exercise regimen did not show these beneficial changes [ 106 , 181 , 182 ]. Moderate physical exercise has been shown to stimulate the expression of endogenous antioxidants such as SOD, GRx, and GR; reduce the activity of NADH oxidase; and reduce the production of inflammatory cytokines such as IL-6 and TNF-α, thereby limiting the spread of oxidative stress [ 183 , 184 ].…”
Section: Nos/no Pathway-involved Vad Therapiesmentioning
confidence: 99%
“…Previous studies indicated that BDNF could increase the production of nitric oxide acting through its receptor tropomyosin-related kinase B (Biojone et al, 2015). In our previous study, we found that 4 weeks of running exercise increased nitric oxide synthase activity, nitric oxide content, and the capillary parameters in the rat hippocampus, and the protective effect of running exercise on the capillaries was weakened when the synthesis of endogenous nitric oxide was blocked (Qi et al, 2020). Therefore, we speculated that the exercise-induced increase in BDNF in the peripheral blood might promote the production of nitric oxide and angiogenesis, and then increase the release of BDNF from cerebral endothelial cells, thus promoting the regeneration of oligodendrocytes and myelination through inhibiting the NogoA downstream signaling pathway in the white matter of aged rats.…”
Section: Discussionmentioning
confidence: 70%
“…Several compensatory mechanisms have been reported, including vertebral artery and basilar artery dilation (Jing et al., 2015 ). The concentration of NO, which has a vasodilating effect, was increased in the blood during cerebral ischemia (Qi et al., 2020 ) and neovascularization (Jing et al., 2015 ). On the 28 th day, T2* values in the cortex and hippocampus in the model group were very close to those in the sham group.…”
Section: Discussionmentioning
confidence: 99%